Biocompatible stimuli‐responsive nanogels for controlled antitumor drug delivery. Issue 12 (20th January 2016) - Aguirre, Garbiñe; Villar‐Alvarez, Eva; González, Adrián; Ramos, Jose; Taboada, Pablo; Forcada, Jacqueline
ABSTRACT: Herein, the synthesis and potential application as cargo delivery systems of thermo‐responsive poly( N ‐vinylcaprolactam) (PVCL)‐based, pH‐responsive poly(2‐(diethylamino)ethyl) methacrylate (PDEAEMA)‐based, and thermo‐, and pH‐responsive PDEAEMA/PVCL‐based core–shell nanogels are reported. All the nanogels have been synthesized using different dextran‐methacrylates (Dex‐MAs) as macro‐cross‐linkers. Doxorubicin hydrochloride (DOXO), an anticancer drug, has been effectively loaded into nanogels via hydrogen‐bonding interactions between OH groups of DOXO and OH groups of Dex‐MA chains. Drug‐release profiles at various pHs, and the cytocompatibility of the DOXO‐loaded nanogels have been assessed in vitro using cervical cancer HeLa and breast cancer MDA‐MB‐231 cell lines. In all the cases, the DOXO release is controlled by Fickian diffusion and case‐II transport, being the diffusional process dominant. In addition, DOXO‐loaded nanogels are efficiently internalized by HeLa and MDA‐MB‐231 cells and DOXO is progressively released in time. Therefore, nanogels synthesized could be suitable and potentially useful as nanocarriers for antitumor drug delivery. © 2016 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem.2016, 54, 1694–1705 Abstract : Thermo‐responsive poly( N ‐vinylcaprolactam)‐based, pH‐responsive poly(2‐(diethylamino)ethyl) methacrylate‐based, and thermo‐ and pH‐responsive PDEAEMA/PVCL‐based core‐shell nanogels are reported, and their suitability for potential nanocarriers for drug delivery are analyzed. Doxorubicin hydrochloride was effectively loaded into the nanogels, the drug release profiles were studied at various pHs, and the cytocompatibility was assessed in vitro using cervical cancer and breast cancer cell lines.